From pond to polymer: A concise review on algae-derived plastics - Akash Phillip; Tushar Chauhan; Shravan Kumar; Bagepalli Srinivas Ashok Kumar (BIORE Scientia Academy, 2026)
Algae-derived plastics signify a revolutionary advancement in the pursuit of sustainable materials, providing a renewable and environmentally benign substitute for conventional petroleum-based polymers. This review explores the most recent advancements in algae cultivation, polymerization methodologies, and synthetic biology that have elevated algae-based bioplastics to a position of prominence. It emphasizes the distinctive characteristics of algal biopolymers, their capacity to sequester carbon, and their various applications, encompassing packaging and 3D printing. Nonetheless, the pathway from aquatic environments to polymeric substances is laden with obstacles, including elevated production costs, challenges related to scalability, and regulatory impediments. Through the analysis of case studies, market dynamics, and burgeoning research, this paper highlights the pivotal importance of algae-derived plastics in fulfilling circular economy objectives and mitigating plastic pollution. The review culminates with an appeal for international collaboration, policy advocacy, and sustained investment in algae bioplastics to realize their complete potential as a fundamental element of sustainable development.